2022
DOI: 10.3390/nu15010011
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Forms and Dosages Determined Their Biological Actions in Mouse Models of Parkinson’s Disease

Abstract: Selenium (Se), an essential antioxidant trace element, is reported to play a role in Parkinson’s disease (PD). However, there is a lack of systematic studies on different Se forms against PD. Our study is designed to compare the neuroprotective effects of inorganic and organic Se in two classical PD mice models and investigate the underlying mechanisms for their potentially differential actions against PD. In this study, different dosages of inorganic sodium selenite (Se-Na) or organic seleno-L-methionine (Se-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…[45] Such findings underscore the necessity of further research to explore selenium's impact across different stages of PD, potentially unveiling stagespecific therapeutic or preventive measures. [46] This aspect aligns with our findings of elevated selenium levels in the CSF of PD patients, suggesting that selenium may play a complex role in the disease's pathophysiology that warrants detailed investigation.…”
Section: Discussionsupporting
confidence: 87%
“…[45] Such findings underscore the necessity of further research to explore selenium's impact across different stages of PD, potentially unveiling stagespecific therapeutic or preventive measures. [46] This aspect aligns with our findings of elevated selenium levels in the CSF of PD patients, suggesting that selenium may play a complex role in the disease's pathophysiology that warrants detailed investigation.…”
Section: Discussionsupporting
confidence: 87%
“…It has been demonstrated that Se levels in the CSF of PD patients were significantly higher than those in controls [ 97 , 98 ]. In experimental studies, Se treatment exhibits neuroprotective effects in parkinsonian models [ 99 , 100 , 101 ]. Ellwanger et al reported that Se administration reduced DNA damage and bradykinesia in parkinsonian rats injected with paraquat, which is a pesticide associated with increased risk for developing PD [ 99 ].…”
Section: Protective Functions Of Mts Against Etiopathogenesis In Pdmentioning
confidence: 99%
“…Ellwanger et al reported that Se administration reduced DNA damage and bradykinesia in parkinsonian rats injected with paraquat, which is a pesticide associated with increased risk for developing PD [ 99 ]. Sun et al demonstrated that administration of sodium selenite increased GPx activity and provided neuroprotective effects in 1-methyl 4-phenyl 1,2,3,6-tetrahydropyridine (MPTP)-injected parkinsonian mice [ 100 ]. It is still unknown whether MTs can function in the maintenance of Se; however, it is reported that sodium selenite induces MTs in mice.…”
Section: Protective Functions Of Mts Against Etiopathogenesis In Pdmentioning
confidence: 99%
“…Therefore, on this basis selenomethionine is commonly used in feed for intensive poultry practices [ 6 , 41 ]. However, the inorganic forms are readily absorbed and in general the available evidence indicates inorganic Se displays enhanced protective effects against certain pathologies, including Parkinson’s disease [ 42 , 43 ]. Thus, sodium selenite has also ameliorated intestinal inflammation and histological damage in colitis mouse models via downregulation of proinflammatory cytokines and certain T-cell populations, with a concomitant upregulation of anti-inflammatory cytokines [ 44 ].…”
Section: Introduction Of Seleniummentioning
confidence: 99%